(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2013)
An efficient protocol was established for in vitro plant regeneration of Paederia foetada L. (Family. Rubiaceae), a widely used medicinal vine of Bangladesh through callus culture in using nodal segment. Yellowish green nodular callus was observed from nodal segments on MS basal medium supplemented with 1.5 mg/L BAP + 0.5 mg/L NAA within three weeks. Large number of shoots (14.4±1.29) were obtained when the callus was sub cultured on MS medium with 0.5 mg/L BAP. In vitro raised shoots rooted on half strength MS medium with 0.5 mg/L IBA. The survival rate of plantlets was found to be 85%. Regenerated plants were morphologically uniform having normal leaf shape and growth. Bangladesh J. Sci. Ind. Res. 47(4), 373-378, 2012 DOI: http://dx.doi.org/10.3329/bjsir.v47i4.14066